The Relationship between Personal Factors and Behavior of Using Personal Protective Equipment on Workers - Arira Celia Virta Parawansa; Naomi Cimera; Ahmad Rido’i Yuda Prayogi; Dani Nasirul Haqi (Universitas Airlangga, 2022)
Introduction: PT. Kerta Rajasa Raya is an industrial manufacturing company in the manufacturing of Woven Bags and Jumbo Bags. From 2012 to 2017, the total incidence of work accidents reached 844 cases. One of the divisions at PT. Kerta Rajasa Raya which often experiences work accidents is the extruder division. The most frequent accidents experienced by workers in the extruder division are being hit by a cutter and pinched by a roll on the machine. One of the causes of accidents is workers' non-compliance with the use of PPE. This study aims to analyze relationship between personal factors and non-compliance behavior in using PPE by workers. Methods: This study used a quantitative approach with an observational analytical method and a cross-sectional design. The population of this study was workers in the extruder division of PT. Kerta Rajasa Raya with sample of 79 workers, who were chosen through a random sampling technique. The data collection was conducted by the means of observation sheets and questionnaires using Kendall test analysis. Results: The results of the study showed that education level (r = 0.220), years of service (r = 0.216), attitude (r = -0.244) and knowledge (r = -0.210) had a weak relationship with the behavior of using PPE. Conclusion: There was an effect in the relationship between education level, years of servicee, attitude, and knowledge of workers in using personal protective equipement.Keywords: behavior, personal factors, personal protective equipment